Critical thinking skills video series for medical assistants : medications, part one. - W.B. Saunders Company; Nick Kaufman Productions; Insight Media (New York, NY : Insight Media, distributor, 2002)
This program stresses the gravity of medication errors, examining the ways in which they occur. It also teaches how to think ciritcally, develop creative problem solving skills, and to make correct decisions in a variety of situations.
No Master.
Keywords: Drugs -- Safety measures; Drugs -- Administration; Medication errors -- Prevention and control; Medical assistants; Critical thinking -- Study and teaching; Problem solving -- Study and teaching